1035325 Faktor-faktor yang Berhubungan dengan Kejadian Anemia Pada Ibu Hamil - Leny (STIKes Budi Mulia Sriwijaya, 2019)
ABSTRACT The World Health Organization (WHO) announces that pregnant women increase substance deficiency by around 35-37%, and it increases with age. Substance deficiency anemia is increasing in developing countries than in developed countries. The purpose of this study was to determine the factors associated with the incidence of anemia in pregnant women at Budi Mulia Medika Clinic in Palembang in 2018. The design of this study was analytic research by discussing cross sectional. The study population was third trimester pregnant women who examined their pregnancy at the Budi Mulia Medika Clinic in Palembang in 2018. The sample was taken by simple random sampling with a total sample of 149 respondents. From the results of the study using the Chi-square statistical test comparing p values with significance level α (0.005) shows there is a relationship associated with anemia in pregnant women where the p value (0,000) is smaller than α (0.005), there is a significant relationship between nutritional status with the incidence of anemia in pregnant women where the p value (0,000) is smaller than α (0.005), and there is a relationship between the mother and the incidence of anemia in pregnant women where the p value (0,000) is smaller than α (0.005). Therefore it is necessary to improve health care facilities for pregnant women who increase anemia by allowing about fixing and correcting anemia during pregnancy, childbirth and the puerperium. Keywords: Genesis Anemia, Age, nutritional status, Parity